Keamanan Aplikasi Web Melalui Penerapan Cross Site Request Forgery(CSRF) - Taufik Ramadan Firdaus (ITEJ (Information Technology Engineering Journals), 2016)
Currently the Internet became one of the media that can not be separated, as well as a wide variety of applications supplied her. As the development of technologies, reliance on Web applications also increased. However, web applications have a wide range of threats, one of it is a CSRF (Cross-Site Request Forgery). This study uses CSRF (Cross-Site Request Forgery) Protection. CSRF (Cross-Site Request Forgery) Protection is a treatment method that has a variety of ways, one of which uses a token in the session when the user login. Token generated at login will be used as a user id that the system of web applications to identify where the request originated. The results of this study are expected in order to increase web application defenses against CSRF (Cross-Site Request Forgery), so that web application users will be able to feel safe in using the Internet and its various feature. Reduced level of attacks on web applications. So that visitor traffic on the web application can be increased.